2021
DOI: 10.1007/s11218-021-09627-w
|View full text |Cite
|
Sign up to set email alerts
|

The influence of in-group and out-group favouritism on the disciplinary practice of ethnic majority and minority preservice teachers

Abstract: Teacher judgments and the disciplinary sanctioning of pupils can be understood as a function of the ethnic match, which means whether or not teachers and pupils have the same ethnic background. According to social identity theory, teachers should be motivated to protect positive self-esteem and therefore favour pupils of their ethnic in-group over pupils of their ethnic out-group. Following system justification theory however, it must be assumed that teachers also base their judgments and their disciplinary be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
1
2
0
1
Order By: Relevance
“…Two studies found that imagined prosocial interaction from a third-person perspective increased altruistic intentions, donation willingness to an out-group organization, and decreased intergroup anxiety compared to other imagined contact situations. These findings are consistent with previous research that has shown how positive behavior with an out-group can influence how individuals feel during the contact, enhance their knowledge about the out-group, and create positive judgments of them (e.g., Schuchart et al, 2021;Whitt et al, 2021). Furthermore, it has been found that positive contact can reduce prejudice by blurring intergroup boundaries.…”
Section: Discussionsupporting
confidence: 91%
“…Two studies found that imagined prosocial interaction from a third-person perspective increased altruistic intentions, donation willingness to an out-group organization, and decreased intergroup anxiety compared to other imagined contact situations. These findings are consistent with previous research that has shown how positive behavior with an out-group can influence how individuals feel during the contact, enhance their knowledge about the out-group, and create positive judgments of them (e.g., Schuchart et al, 2021;Whitt et al, 2021). Furthermore, it has been found that positive contact can reduce prejudice by blurring intergroup boundaries.…”
Section: Discussionsupporting
confidence: 91%
“…B. Downey & Pribesh, 2004;Dunkake & Schuchart, 2015;Glock & Kleen, 2017), dass von ihnen auch in der Zukunft häufiger regelbrechendes Verhalten erwartet wird (Okonofua & Eberhardt, 2015) und dass sie auch bei gleichem Verhalten häufiger und härter durch Lehrkräfte sanktioniert werden (Glock & Schuchart, 2019;Schuchart, Glock & Dunkake, 2021;Skiba, Horner, Chung, Rausch, May & Tobin, 2011; siehe auch Glock & Baumann in diesem Band). Personen, die überdies glauben, dass der soziale Status das Ergebnis stabiler Eigenschaften ist, sind eher bereit, hart zu sanktionieren (Kraus & Keltner, 2013).…”
Section: Lehrendeunclassified
“…Notably, Adida et al (2017)'s concept of ‘ethnically motivated reasoning’ builds on Tajfel's (1974) social identity theory: their field experiment on ethnic voting in Benin shows that citizens do not only vote for coethnic politicians because they expect their region to be favoured by policies or redistribution, but also because citizens derive self-esteem and pride from seeing their group do well compared with others (see Adida et al 2017). Likewise, research on education and discrimination in Western contexts suggests that teachers, often unconsciously, favour coethnic pupils to protect the positive image of their in-group (Schuchart et al 2021; see also Kleen et al 2019). ‘Ethnically motivated reasoning’ would moreover allow citizens – here, teachers – to affirm their status as ‘good’ members of their group (Adida et al 2017).…”
Section: Conceptualising Ethnic Favouritism Among Teachersmentioning
confidence: 99%
“…Teachers may, however, also favour pupils from their own kin without being aware of it. Such unconscious behaviour (often non-verbal communication) can cause ethnic disparities too in, for instance, penalising misconduct (see van den Bergh et al 2010; Kleen et al 2019; Schuchart et al 2021). It is important to note in this respect that, like anybody else, teachers have a tendency to exhibit implicit preferences for the in-group (for a case study among Kenyan teachers, see Kuppens et al .…”
Section: Conceptualising Ethnic Favouritism Among Teachersmentioning
confidence: 99%